2002
DOI: 10.1086/339202
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Outcome of Mould Infections in Hematopoietic Stem Cell Transplant Recipients

Abstract: Reports have focused on the emergence of moulds as pathogens in recipients of hematopoietic stem cell transplants. To review the incidence of and risks for mould infections, we examined the records of 5589 patients who underwent hematopoietic stem cell transplantation at the Fred Hutchinson Cancer Research Center (Seattle) from 1985 through 1999. After 1992, the incidence of invasive aspergillosis increased in allograft recipients and remained high through the 1990s. Infections with non-fumigatus Aspergillus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
934
6
32

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,295 publications
(993 citation statements)
references
References 26 publications
21
934
6
32
Order By: Relevance
“…Pneumocystosis, endemic fungal infections, and cryptococcosis were rarely encountered in the HSCT population. Consistent with prior reports [4][5][6][7], mortality was high and one-year survival was low for HSCT patients with IFI. Fusarium infections and IA were associated with the lowest one year survival (6% and 25%, respectively); however, survival among patients with zygomycosis (28%) and IC (34%) was not substantially better.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Pneumocystosis, endemic fungal infections, and cryptococcosis were rarely encountered in the HSCT population. Consistent with prior reports [4][5][6][7], mortality was high and one-year survival was low for HSCT patients with IFI. Fusarium infections and IA were associated with the lowest one year survival (6% and 25%, respectively); however, survival among patients with zygomycosis (28%) and IC (34%) was not substantially better.…”
supporting
confidence: 91%
“…While cryptococcosis has been most commonly encountered in the HIV infected population [52], a multicenter study reporting 306 cases of cryptococcosis in non-HIV-infected patients found 0.7% of total cases occurred in HSCT recipients, 18% in SOT recipients, 9% in patients with hematologic malignancies, and 9% in patients with other malignancies [53]. Other U.S. studies have found similarly low rates of cryptococcal infection in the HSCT population [1,5,54], most likely owing to use of routine fluconazole prophylaxis following HSCT. The overall mortality for cryptococcosis in the non-HIV population was 30%, attributable mortality 12%, and hematologic malignancy as an underlying diagnosis was associated with decreased survival [53].…”
Section: Cryptococcusmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, at the Fred Hutchinson Cancer Research Center in Seattle, the proportion of infections caused by non- fumigatus Aspergillus species increased during the latter 1990s. Most of these infections were caused by A. flavus , A. nidulans , A. terreus , and A. niger ( 3 ). …”
mentioning
confidence: 99%
“…Rhinocerebral mucormycosis is the most common form of mucormycosis that occurs in patients having diabetic ketoacidosis, haemotological malignancies and haemopoietic stem cell transplant. Patient having haemotological malignancies develop mucormycosis due to prolonged corticosteroid therapy which causes immunosuppression, chemotherapy induced neutropenia and repeated blood transfusion leading to iron overload which was also observed in the reported patient [14,15]. Patients of rhinocerebral mucormycosis clinically present with facial pain, numbness, nasal congestion and conjunctival suffusion.…”
Section: Discussionmentioning
confidence: 82%